Dívida pública, política fiscal e nível de atividade: Uma abordagem VAR para o Brasil no período 1995-2008 - Marco A. F. H. Cavalcanti; Napole\~ao L. C. Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– In this paper we investigate the real effects of fiscal policy in Brazil during the 1995-2008 period by estimating a VAR model that explicitly takes into consideration the role of public debt in the determination of fiscal variables, as recommended by Favero and Giavazzi (2007). According to our results, it really makes a difference whether one takes into account the public debt's role in the fiscal policy process; more specifically, models that omit the public debt are likely to overestimate the real effects of fiscal policy shocks.
Keywords: E13; E6; 330; Finanzpolitik; Wirkungsanalyse; Öffentliche Schulden; VAR-Modell; Brasilien